How genetic determinism and essentialism relate to health care - Choirunisa', Nindiana; Zubaidah, Siti; Susanto, Hendra; Chang, Chun-Yen (International Journal of Public Health Science (IJPHS), 2025)
Genetics has become important in various areas of life, especially in healthcare. People can undergo a range of genetic testing to assess their susceptibility to acquiring diseases. Nevertheless, data derived from genetic testing might indicate bias due to genetic determinism and essentialism. This study aimed to provide a comprehensive analysis of the impact of genetic determinism and essentialism on several aspects of healthcare. This study conducted a systematic review approach using the Scopus database and followed the preferred reporting items for systematic reviews and meta analysis (PRISMA) search framework. We initially received 802 publications, then reduced to 49 articles based on inclusion and exclusion criteria, and then content analysis was conducted. Our research showed that determinist bias and genetic essentialism may reduce patient diagnosis, treatment accuracy, and effectiveness. Moreover, biases related to genetic determinism and essentialism may go against healthcare regulations and cause discrimination and other negative clinical outcomes from ethical, social, and legal aspects. To improve this problem, it is essential for laypeople, particularly medical experts, to understand genetic principles related to the development of variances in traits among individuals in a precise and relatable approach.